Mixed methods evaluation of the COVID-19 changes to the WIC cash-value benefit for fruits and vegetables - Allison M. Nitto; Mayra Crespo-Bellido; Jackie Yenerall; Elizabeth T. Anderson Steeves; Sarah K. Kersten; Daniele Vest; Jennie L. Hill; Jennie L. Hill (Frontiers Media S.A., 2024)
IntroductionRecent cash-value benefit (CVB) increases are a positive development to help increase WIC participant fruits and vegetables (FV) access. Little is known about the impacts of the CVB changes on FV redemptions or about implementation successes and challenges among WIC State and local agencies. This mixed method study aimed to evaluate (a) the CVB changes' impact on FV access among WIC child participants measured by CVB redemption rates, (b) facilitators and barriers to CVB changes' implementation, and (c) differences in FV redemption and facilitators and barriers by race/ethnicity.MethodsWe requested redemption data from all 89 State agencies for April 2020 to September 2022 and utilized descriptive statistics, interrupted time series analysis (ITS), and generalized linear regression analysis. Additionally, we recruited State agencies, local agencies, and caregivers across the U.S. for interviews and used rapid qualitative analysis to find emerging themes anchored in policy evaluation and implementation science frameworks.ResultsWe received redemption data from 27 State agencies and interviewed 23 State agencies, 61 local agencies, and 76 caregivers of child WIC participants. CVB monthly redemptions increased at $35/child/month compared to $9/child/month; however, adjusted ITS analyses found a decrease in redemption rates at $35/child/month. The decrease was not significant when the transition/first implementation month was excluded with rates progressively increasing over time. Differences were found among racial/ethnic groups, with lower redemption rates observed for non-Hispanic Black caregivers. Overall, WIC caregivers reported high satisfaction and utilization at the $35/child/month. The frequent and quick turnaround CVB changes strained WIC agency resources with agencies serving higher caseloads of diverse racial and ethnic populations experiencing greater issues with implementing the CVB changes.ConclusionDespite implementation challenges, the increased CVB shows promise to improve WIC participant FV access and satisfaction with WIC. WIC agencies need adequate lead time to update the CVB amounts, and resources and support to help ensure equitable distribution and utilization of the FV benefits.